Shredded-Coconut-Derived Sulfur-Doped Hard Carbon via Hydrothermal Processing for High-Performance Sodium Ion Anodes - Yuanfeng Liu; Shuai Chen; Chengzhi Zhang; Guochun Li; Junfeng Liu; Yong Wang (Nanomaterials)
The extensive use of sodium-ion batteries has made it important to develop high-performance anode materials. Owing to their good sustainability, low cost, and excellent electrochemical properties, hard carbon materials are expected to be a good choice, especially biomass-derived hard carbon. In this study, we successfully synthesized a coir-based carbon nanosphere as an anode material. The hard carbon has a low degree of structural ordering, small particle size, and multiple pore networks for easy sulfur doping compared to the conventional direct high-temperature sulfur doping. The material has a high reversible capacity of 536 mAh g−1 and an initial Coulombic efficiency of 53%, maintaining a reversible capacity of 308 mAh g−1 at a high current density of 5 A g−1, achieving a capacity retention of 90.3% after 1000 cycles. The performance enhancement stems from a combination of enlarged layer spacing, an increased specific surface area, enhanced porosity, and doped sulfur atoms. This study provides an effective strategy for the conversion of biomass waste into high-performance sodium-ion anode material batteries.